2022
DOI: 10.5152/auaf.2022.910123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additional Boron Fertilization on Growth and Yield of Broccoli (Brassica oleracea L. var. italica Plenck)

Abstract: Brokkoli (Brassica oleracea L. var. italica Plenck)'de İlave Bor Gübrelemesinin Gelişme ve Verim Üzerine Etkisi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…treatment. The findings of the experiment were in coincided with the findings of [8]. They reported that seedling age of four weeks gave best results.…”
Section: Plant Heightsupporting
confidence: 83%
See 1 more Smart Citation
“…treatment. The findings of the experiment were in coincided with the findings of [8]. They reported that seedling age of four weeks gave best results.…”
Section: Plant Heightsupporting
confidence: 83%
“…Cristiaini et al [13] found the similar result in cauliflower. Kaymak et al [8] reported that curd diameter (6.4 cm) was also observed from 30 day-old transplants in cauliflower.…”
Section: Diameter Of Knob Per Plantmentioning
confidence: 94%
“…lainnya yang satu keluarga dengan sawi menginformasikan bahwa umur bibit berpengaruh terhadap pertumbuhan dan hasil tanaman. Umur bibit saat pindah tanam berpengaruh terhadap pertumbuhan serta hasil dan umur bibit yang lebih muda cenderung meningkatkan hasil tanaman (Kaymak, et al, 2009). Penggunaan umur bibit yang tepat memberikan hasil tertinggi pada kubis Cina yang dibudidayakan di musim semi dan musim gugur namun pindah tanam yang terlalu awal berdampak pada penurunan hasil dan pengurangan unit massa krop (Krezel and Kolota, 2009).…”
Section: Pendahuluanunclassified